Comparison of Methods for Computation of Electron Optical System Potential Distribution - Šumskienė, L.; Virbalis, J. A. (Elektronika ir Elektrotechnika, 2005)
To calculate the electrostatic field of electron gun was used software ANSYS. ANSYS is based on FEM. Model of electron gun is complicated enough, so we used submodeling. Test precision of calculated electrostatic field potential values was used simple immersion lens. The computed values by FEM using submodeling were in comparison with values computed in analytical way. They were very close, when the finite element size of submodel was four times smaller than the element size of coarse model. Ill.10, bibl. 4. (in Lithuanian; summaries in Lithuanian, English, Russian).